A Study on the Vocational Education in the Asean Economic Community (AEC) Countries and ITS Implications to Indonesia - Albert, Albert (Universitas Semarang, 2020)
ASEAN Economic Community (AEC) is a regional program which started in 2015, was developed by members of ASEAN countries which have agreed on pillars on mutual collaboration to increase the economic and social growth. The AEC has agreed to carry out four major pillars: (1) single market and production base, (2) competitive economic region, (3) equitable economic development and (4) integration into global economy. The four pillars are divided into 17 core elements, and among the core element, there is one particular core element which focuses on human resources which is the free flow of skilled labours. The government of the ASEAN countries have taken actions towards anticipating the ASEAN Economic Community (AEC), especially in regards to the free flow of skilled labour. One of actions is improving the quality of education. Some countries have invested high amount of funds in order to increase the quality of graduates. Indonesia has also started to make improvements in the quality of education. One of the improvement was in the form of constructing Indonesian Qualification Framework (IQF) which were then obliged for all education institution to follow. However, related to the vocational education, more beneficial collaborations with the industry should be carried out. Also, other soft skills which are required in workplace still need to be formally included in the assessment process of the education